HUBUNGAN SUDUT KAKI DAN FREKUENSI REPETISI DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA TUNGKAI BAWAH OPERATOR JAHIT PO. SEVENTEEN GLORY SALATIGA - Kartika Weningtyas; Baju Widjasena; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2017)
Musculoskeletal disorders are injuries and disorders that affect musculoskeletal system such as muscles, bones and joints. Foot posture (measured by angle) and high task repetition may be a risk factor for lower limb disorders among sewing operators. The aim of this study was to identify the association of foot angle and frequency repetition in sewing operators with musculoskeletal disorders at lower extremities. This type of research is cross sectional study with observasional study and descriptive analytic. Population of this research is sewing operators totaling 35 people. The sample in this study were drawn from total population. Musculoskeletal disorders was measured subjectively using Body Map Questionnaire. Statistical analysis is using Rank Spearman correlation test. The results showed there are no correlation between knee angle with musculoskeletal disorders at knee (sig = 0,236), lower leg (sig = 0,868), ankle (sig = 0,518) and foot (sig = 0,156) also between ankle angle with musculoskeletal disorders at knee (sig = 0,154), lower leg (sig = 0,227), ankle (sig = 0,334) and foot (sig = 0,342). There is a correlation between frequency repetition with musculoskeletal disorders at knee (sig = 0,044), lower leg (sig = 0,025), ankle (sig = 0,031) and foot (sig = 0,001). Business owner should give pattern rotation or work rotation among sewing operators to decrease repetitive motion.